VARIASI BAHASA HUMOR DALAM OPERA VAN JAVA - Amalia, Rizqi; Amir, Johar; Fitri, Sakinah (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2024)
This study aims to describe the forms and variations of humor language in Opera Van Java and to analyze the variations of humor language in the show. This research uses a qualitative descriptive method. The data for this study consists of dialogues between the actors containing utterances that include humorous elements, spoken in Opera Van Java. The techniques used in this study include observation, documentation, as well as the listening and note-taking technique. The data analysis involves data presentation, data reduction, and then drawing conclusions. The results of the study show that the forms of humor in Opera Van Java are: one-liner humor, two-line humor, dialogue humor, topic sentence humor, malapropism humor, and wordplay humor. Meanwhile, the variations of humor language in Opera Van Java include personal humor, social humor, physical humor, and graphic humor.